A Structured Literature Review of Corporate Governance and Performance Research Within an Emerging Country Setting - Camelia Iuliana Lungu; Pompei Mititean; Chirata Caraiani; Daniela Constantinescu (Journal of Accounting and Management Information Systems (JAMIS), 2020)
Research Question: The research proposition is to identify the particular interest of researchers, their work visibility and features, as well as the trend in the literature for corporate governance and corporate performance area of research from an emerging country perspective. Motivation - The relationship between corporate governance and company performance is a widely debated topic in the literature. Regardless of the popularity of the topic addressed in the accounting literature, little research focused on carrying out a structured literature review in emerging countries. Idea - The objective of this study is to debate on the relevance that the Romanian researchers has given to the study of the corporate governance and performance relationship. Data - The database selected for the research is Web of Science, counting a total number of 114 papers included in the study. Tools - A Structured Literature Review (SLR) is conducted, analysing the research published by the Romanian academics, referring to corporate governance and the performance of the companies. Findings - The results illustrate multiple waves both in the interest of the researchers, as well as in the validation of their research. Most of the studies engage a quantitative methodology, focusing on the national companies' policies of corporate governance. Furthermore, the authors concentrate within three main universities in the country. Contribution - This paper provides an approach to discover under-investigating topics and methods, thus being a starting point for researchers who will further study this subject. It may have direct implications especially in the academic environment of the European emerging countries.
Keywords: M41; G34; 650; Structured literature review; Corporate governance; Corporate performance; Emerging countries.